2017
DOI: 10.19085/journal.sijmd040601
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Preference Towards the Mobile Wallets Among the University Students in Lucknow City

Abstract: Few years back mobile wallet was something majority in India did not hear about but its use saw a huge leap in last couple of years with the surge of smart phones, high speed internet connectivity using 3G and 4G and the lucrative offers mobile wallets provide. This research paper is an attempt to study the preference towards mobile wallet among the students studying in various universities in Lucknow city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Kekurangan uang elektronik yaitu ketergantungan dengan battery smart phone sangat tinggi; penggunakan hanya untuk pembayaran cashless sehingga sisa saldo tidak bisa ditunaikan; penggunaan dompet digital hanya terbatas pada merchant yang dijadikan patner (PT Bank Danamon Indonesia Tbk, 2021). Menurut Shailendra Singh Rana (2017), pemilihan uang elektronik karena nilai tambah yang dimiliki yaitu pengehematan waktu untuk pembayaran karena menghindari antrean, tempat pembelian bebas dan juga aman dalam bertransaksi (Rana, 2017).…”
Section: Preferensi Pembayaranunclassified
“…Kekurangan uang elektronik yaitu ketergantungan dengan battery smart phone sangat tinggi; penggunakan hanya untuk pembayaran cashless sehingga sisa saldo tidak bisa ditunaikan; penggunaan dompet digital hanya terbatas pada merchant yang dijadikan patner (PT Bank Danamon Indonesia Tbk, 2021). Menurut Shailendra Singh Rana (2017), pemilihan uang elektronik karena nilai tambah yang dimiliki yaitu pengehematan waktu untuk pembayaran karena menghindari antrean, tempat pembelian bebas dan juga aman dalam bertransaksi (Rana, 2017).…”
Section: Preferensi Pembayaranunclassified
“…The study revealed the challenges, an organization faced to sustain in this market [1]. Shailendra Singh Rana studied on the preferences towards mobile wallet by developing of smart phones and high-speed internet connectivity using 3G and 4G [11]. P.Sarika, S.Vasantha studied on…”
Section: Review Literaturementioning
confidence: 99%